Preparation method of CoFe LDH catalyst and application of CoFe LDH catalyst in electrocatalytic oxidation of HMF

By introducing sulfur-filled oxygen vacancies into the CoFe LDH catalyst, S-Ov-CoFe LDH is solved, and the problem of excessive adsorption of oxygen-rich CoFe LDH catalysts in electrocatalytic HMF oxidation is achieved, low overpotential and high FDCA yields are achieved , demonstrates excellent catalytic performance and structural stability.

CN119194503APending Publication Date: 2024-12-27QINGDAO UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411393505.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, the oxygen-rich CoFe LDH catalyst has excessive adsorption of reactants HMF and OH species during electrocatalytic HMF oxidation, resulting in high overpotentials and limited catalytic activity, which fails to meet the demand.

Method used

CoFe LDH is synthesized by hydrothermal method, converted into CoFe MOF, and then etched in an alkaline solution to form an oxygen-rich defective CoFe LDH, and sulfur atoms are filled with oxygen vacancies by sulphur leaching to form an S-Ov-CoFe LDH catalyst, optimized Its adsorption behavior and energy band structure.

Benefits of technology

The S-Ov-CoFe LDH catalyst exhibits excellent performance in electrocatalytic HMF oxidation, with reduced overpotential, FDCA yield reaching more than 96%, fast kinetic rate, stable structure, and low raw material cost, which is suitable for large-scale promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194503A_ABST
    Figure CN119194503A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electro-catalysis, and relates to a preparation method of a CoFe LDH catalyst and application of the CoFe LDH catalyst in electro-catalytic oxidation of HMF. Converting the CoFe LDH material into a CoFe MOF material by a solvothermal method, and etching the CoFe MOF material through an alkaline solution to obtain a CoFe LDH material rich in oxygen defects; and then the oxygen-rich defect CoFe LDH material is subjected to sulfur soaking treatment, and the defect position sulfur-filled CoFe LDH catalyst material is obtained. According to the preparation method, MOF serves as a precursor for the first time, an in-situ structure is converted to generate oxygen-rich defect LDH, oxygen vacancies are filled with sulfur, and the cobalt-iron-based hydrotalcite with the oxygen vacancies filled with sulfur and of a nanosheet structure is obtained; the material is stable in structure and low in overpotential during electro-catalysis of HMF oxidation, and the FDCA yield can reach 95% or above; the preparation method is ingenious, simple, low in cost, rich in raw material source, suitable for large-scale popularization and wide in market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of electrocatalysis, and particularly relates to a preparation method of a defect-site sulfur-filled CoFe LDH catalyst and application thereof in the electrocatalytic oxidation of HMF. Background technology:

[0002] In view of the current severe energy and environmental problems, it is imperative to develop new clean energy to balance the relationship between energy demand and environmental protection. Biomass, as a resource-rich renewable energy, has attracted widespread attention from researchers in recent years. Due to the presence of multiple functional groups, biomass-derived 5-hydroxymethylfurfural (HMF) can be catalytically converted into a variety of value-added chemicals and is considered to be an important platform compound. Among the many catalytic downstream products, 2,5-furandicarboxylic acid is used as a green alternative to petroleum-based terephthalic acid, which has great application potential and economic value. Recently, due to the advantages of operating conditions at room temperature and pressure, the attention to electrocatalytic HMF conversion has gradually increased.

[0003] Benefiting from the abundant metal sites in the laminae, hydrotalcite (LDH) shows good development potential in the field of HMF oxidation. However, due to its weak intrinsic properties, the catalytic performance of this material is low, which still has a wide room for improvement. Therefore, it is of great significance to adopt appropriate modification strategies to further improve the catalytic oxidation activity of HMF.

[0004] Defect engineering can adjust the degree of electron localization and change the band structure of the catalyst, thereby affecting the adsorption behavior of reactants and intermediates, and is considered to be an ideal way to improve the catalytic activity of materials. So far, researchers have developed some catalysts rich in oxygen vacancies, showing enhanced adsorption capacity and improved activity. In fact, according to the Sabatier principle, the optimal catalyst should maintain a moderate adsorption strength with the reactant species to balance the relationship between adsorption coverage and product desorption. Although the introduction of oxygen vacancies improves the adsorption capacity of reactants and improves catalytic performance, excessive adsorption also inhibits the desorption of products, which in turn limits the optimal expression of activity. At present, no reports have been found on how to modulate oxygen defects in electrocatalytic materials to achieve optimal performance. Summary of the invention:

[0005] The purpose of the present invention is to solve the above technical problems and provide a method for preparing a defect-site sulfur-filled CoFe-LDH catalyst and its application in the electrocatalytic oxidation of HMF, so that the oxygen vacancies of the oxygen-rich defect CoFe LDH are filled with sulfur to achieve the best adsorption performance.

[0006] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing a CoFe LDH catalyst filled with sulfur in defect sites, the material comprising a substrate and a cobalt-iron-based hydrotalcite with sulfur-filled oxygen defects grown on the surface of the substrate, comprising the following steps:

[0007] (1) synthesizing CoFe LDH material by a hydrothermal method, specifically: mixing cobalt salt and iron salt to obtain a mixed solution, reacting the mixed solution with a substrate under hydrothermal conditions, and taking out the substrate after the reaction to obtain the CoFe LDH material;

[0008] (2) converting the CoFe LDH material into the CoFe MOF material by a solvothermal method, specifically: placing the CoFe LDH material in an organic solvent, and performing a mixed reaction at a certain temperature and autogenous pressure of the solution to obtain the CoFe MOF material;

[0009] (3) Using CoFe MOF material as a precursor, etching with an alkaline solution at room temperature to obtain CoFe LDH with abundant oxygen vacancies, the specific steps are: placing the CoFe MOF material in an alkaline solution of a certain concentration and slowly etching it to obtain a CoFe LDH material rich in oxygen vacancies;

[0010] (4) The obtained oxygen-defective CoFe LDH is treated by sulfur immersion, and S atoms fill the oxygen vacancies to obtain S-Ov-CoFe LDH. The specific steps are: immersing the oxygen-defective CoFe LDH material in a sulfur-containing solution to obtain the S-Ov-CoFe LDH material.

[0011] The molar ratio of the cobalt salt and the iron salt added in the present invention is 1-4:1, and the molar ratio of the cobalt ions in the cobalt salt and the iron ion atoms in the iron salt is 24-30:10-18.

[0012] The material of the substrate of the present invention is foamed nickel or foamed copper, carbon fiber or carbon cloth.

[0013] The invention cleans the foam nickel before use: in order to remove the oxide layer and residual organic matter on the surface of the foam nickel, the foam nickel is respectively placed in dilute hydrochloric acid, acetone and ethanol for ultrasonic cleaning, and then the washed foam nickel is taken out, vacuum dried and stored to obtain the foam nickel.

[0014] The cobalt salt described in the present invention is cobalt nitrate or cobalt chloride.

[0015] The iron salt described in the present invention is ferric nitrate or ferric chloride.

[0016] The hydrothermal conditions of the present invention are: keeping warm at 120-160° C. for 4-8 hours.

[0017] The solvent thermal conditions of the present invention are: keeping warm at 180-200° C. for 10-12 hours.

[0018] The alkaline solution of the present invention is a KOH or NaOH aqueous solution.

[0019] The etching conditions of the present invention are: 3-12 hours at room temperature.

[0020] The sulfur soaking treatment conditions of the present invention are: keeping warm at 60-100°C for 0.5-2 hours.

[0021] The sulfur-containing solution of the present invention is a pentahydrate sodium thiosulfate aqueous solution, a nonahydrate sodium sulfide aqueous solution, a thiourea aqueous solution or a thioacetamide aqueous solution.

[0022] The present invention also provides the use of the S-Ov-CoFe LDH material prepared by the method in the electrocatalytic oxidation of HMF, which is used for the electrocatalytic oxidation of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid.

[0023] The present invention overcomes the problem that oxygen-rich defect CoFe LDH has too strong adsorption on reactants HMF and OH species, and the overpotential of electrocatalytic oxidation of HMF by oxygen-rich defect CoFe LDH is large and cannot meet current needs. The LDH obtained by in-situ structural transformation using MOF as a precursor in the present invention has a large number of irregular pores. This unique crystal structure not only helps to expose the highly active sites of unsaturated coordinated metals, but also facilitates electrolyte penetration, thereby promoting mass transfer and charge transfer dynamics. Secondly, the catalyst includes the participation of variable-valence metal cobalt and the filling of oxygen vacancies by heteroatom S. By forming a metal-S bond to modulate the d band structure, the rapid formation of high-valence catalytic sites in the reaction is accelerated, the adsorption behavior of HMF and OH species is optimized, the HMF oxidation activity is greatly improved, and the reaction potential required for electrocatalytic conversion of biomass is reduced.

[0024] Compared with the prior art, the S-Ov-CoFe LDH prepared by the present invention has the following beneficial effects:

[0025] (1) S-Ov-CoFe LDH has excellent HMF electrocatalytic oxidation performance. In 1 M KOH electrolyte, when the current density is 50 mA cm -2 When the overpotential of S-Ov-CoFe LDH was only 1.39 V vs RHE, the FDCA yield could still reach more than 96% after 5 cycles, exceeding that of a large number of CoFe-based electrocatalysts. The catalyst structure remained good after five consecutive electrolysis cycles.

[0026] (2) The electrocatalyst material of the present invention has better adsorption behavior and faster kinetic rate in electrocatalytic HMF oxidation.

[0027] (3) The raw materials used in the present invention are all non-precious metal materials, which are low in price and abundant in reserves.

[0028] (4) The present invention prepares oxygen-rich defect CoFe LDH by a liquid phase method for the first time. The material is in full contact with the solution, so that the defects are not only distributed on the surface of the material, but also more evenly distributed.

[0029] In summary, the present invention is the first to use MOF as a precursor to in-situ structural transformation to generate oxygen-rich defect LDH, and fill the oxygen vacancies with sulfur to obtain a nano-sheet structure of sulfur-filled oxygen-deficient cobalt-iron-based hydrotalcite; the material has a stable structure and a low overpotential during electrocatalytic HMF oxidation, and the FDCA yield can reach more than 95%; the preparation method is ingenious, simple, low-cost, and has abundant raw material sources, which is suitable for large-scale promotion and has broad market prospects. Description of the drawings:

[0030] Figure 1 This is the XRD pattern of the S-Ov-CoFe LDH catalyst prepared in Example 1 of the present invention.

[0031] Figure 2 This is a SEM image of the S-Ov-CoFe LDH catalyst prepared in Example 1 of the present invention.

[0032] Figure 3 This is the HRTEM image of the S-Ov-CoFe LDH catalyst prepared in Example 1 of the present invention.

[0033] Figure 4 This is the XPS graph of the S-Ov-CoFe LDH catalyst prepared in Example 1 of the present invention.

[0034] Figure 5 This is a TEM image of the Ov-CoFe LDH catalyst prepared in Example 1 of the present invention.

[0035] Figure 6 This is a current density-voltage relationship diagram of CoFe LDH, Ov-CoFe LDH and S-Ov-CoFe LDH prepared in Example 1 of the present invention when used as electrodes to catalyze the oxidation of HMF.

[0036] Figure 7 This is a stability test chart of the catalytic oxidation of HMF by S-Ov-CoFe LDH prepared in Example 1 of the present invention.

[0037] Figure 8 This is a graph showing the HMF oxidation performance of the S-Ov-CoFe LDH electrode prepared in Example 1 of the present invention during five consecutive electrolysis processes.

[0038] Fig. 9 The S-Ov-CoFe LDH catalyst prepared in Example 1 of the present invention and other catalysts have a high conductivity at 10 mA cm -2A comparison of the potentials required is shown below.

[0039] Fig.10 This is the R space spectrum of the S-Ov-CoFe LDH catalyst involved in the present invention. Specific implementation method:

[0040] The present invention will be further described below through specific embodiments in conjunction with the accompanying drawings.

[0041] Embodiment 1:

[0042] The present invention relates to a method for preparing a defect-site sulfur-filled CoFe-LDH catalyst (S-Ov-CoFe LDH) material, wherein the material comprises a foamed nickel substrate and cobalt-iron-based hydrotalcite grown on the surface of the foamed nickel substrate, and comprises the following steps:

[0043] (1) Substrate cleaning: The nickel foam was sequentially placed in a 2M hydrochloric acid solution, acetone, and anhydrous ethanol for ultrasonic cleaning for 15 minutes, and then the washed nickel foam was taken out and vacuum dried for storage;

[0044] (2) Preparation of CoFe LDH material:

[0045] 3.75 mmol of cobalt nitrate hexahydrate, 1.25 mmol of ferric nitrate nonahydrate, 4.33 mmol of urea and 2.16 mmol of ammonium fluoride are placed in 30 mL of deionized water and stirred for 20 minutes to obtain a mixed solution; the mixed solution is transferred to a 50 mL reactor, and a piece of nickel foam obtained in step (1) is placed in the reactor as a substrate, and the reactor is placed in a 120° C. oven for reaction for 6 hours; after the reaction is completed, the reactor is cooled to room temperature, and then the nickel foam with the material is taken out, and the nickel foam is rinsed with deionized water and anhydrous ethanol respectively, and dried at 60-80° C. and stored to obtain CoFe LDH material;

[0046] (3) Preparation of CoFe MOF materials:

[0047] 0.5 mmol of 4-4-biphenyldicarboxylic acid was placed in 30 ml of N,N-dimethylformamide and ultrasonicated for 1 hour, and then transferred to a 50 ml reactor, and the CoFe LDH material obtained in step (2) was added to the reactor, and then the reactor was placed in an oven at 180° C. for reaction for 12 hours; after the reaction was completed, the reactor was cooled to room temperature, and then the reacted material was taken out, rinsed with deionized water and ethanol respectively, dried at 60-80° C., and stored to obtain the CoFe MOF material;

[0048] (4) Preparation of CoFe LDH materials rich in oxygen defects:

[0049] The CoFe MOF material obtained in step (3) is placed in a 0.1M KOH aqueous solution and etched at room temperature for 6 hours. After the reaction is completed, the material is taken out, rinsed with deionized water and ethanol respectively, dried at 60-80°C, and stored to obtain an oxygen-defect-rich CoFe LDH material;

[0050] (5) Preparation of S-Ov-CoFe LDH material:

[0051] The oxygen-deficient CoFe LDH material obtained in step (4) is placed in a 0.1M Na2S2O3·5H2O (sodium thiosulfate pentahydrate) aqueous solution and reacted at 70°C for 0.5h. After the reaction is completed, the material is taken out, rinsed with deionized water and ethanol in turn, dried at 60-80°C, and stored to obtain the S-Ov-CoFe LDH material.

[0052] The prepared material in this example is characterized by XRD (X-ray diffraction), SEM (scanning electron microscope), HRTEM (high resolution transmission electron microscope), XPS (photoelectron spectrometer), XAFS (synchrotron radiation) and TEM (transmission electron microscope) and R space spectrum. The results are as follows: Figure 1-5 , Fig.10 And as shown in Table 1.

[0053] from Figure 1 It can be seen from the XRD diagram that: except for the diffraction peak of metallic nickel (scraped from the nickel foam), the standard card of S-Ov-CoFe LDH and CoFe LDH still corresponds well, that is, after the sulfur atoms are filled, the crystal structure of the material has not changed significantly, and the octahedral layered CoFe LDH structure is still maintained.

[0054] from Figure 2 It can be seen from the SEM image that the morphology of the material is curled and wrinkled nanosheets.

[0055] from Figure 3 It can be seen from the HRTEM image that after sulfur filling, the material still retains the (012) crystal plane structure of CoFe LDH, which is consistent with the XRD results.

[0056] from Figure 4 XPS graph, XAFS and Fig.10 It can be seen from the R-space map results that the introduction of S fills the oxygen vacancies in the second shell and forms metal-S bonds, indicating that sulfur atoms are successfully filled in the oxygen-rich defect CoFe LDH material.

[0057] from Figure 5It can be seen from the TEM image that Ov-CoFe LDH has a large number of irregular pores, which are mainly formed based on the structural transformation and chemical treatment of the material and will not cause serious damage to the main structure of the material. Therefore, the S-Ov-CoFe LDH catalyst prepared in this example has a stable structure.

[0058] Table 1. Structural information of the three catalysts

[0059]

[0060] Embodiment 2:

[0061] This embodiment relates to a method for preparing a defect site S-filled CoFe-LDH catalyst (S-Ov-CoFe LDH) material, the material comprising a nickel foam substrate and cobalt-iron-based hydrotalcite grown on the surface of the nickel foam substrate, comprising the following steps:

[0062] (1) Substrate cleaning: the steps are the same as those in Example 1;

[0063] (2) Preparation of CoFe LDH material:

[0064] 4.35 mmol of cobalt chloride hexahydrate, 1.65 mmol of ferric nitrate nonahydrate, 4.33 mmol of urea and 2.16 mmol of ammonium fluoride are placed in 30 mL of deionized water and stirred for 20 minutes to obtain a mixed solution; the mixed solution is transferred to a 50 mL reactor, and a piece of nickel foam obtained in step (1) is placed in the reactor as a substrate, and the reactor is placed in a 150° C. oven for reaction for 6 hours; after the reaction is completed, the reactor is cooled to room temperature, and then the nickel foam with the material is taken out, and the nickel foam is rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain a pure CoFe LDH material;

[0065] (3) Preparation of CoFe MOF materials:

[0066] 0.5 mmol of 1,3-benzenedicarboxylic acid was placed in 30 ml of N,N-dimethylformamide and ultrasonicated for 1 hour, then transferred to a 50 ml reactor, and the reactor was placed in an oven at 180°C for reaction for 10 hours; after the reaction was completed, the reactor was cooled to room temperature, and then the converted material was taken out, and the nickel foam was rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain CoFe MOF material;

[0067] (4) Preparation of CoFe LDH materials rich in oxygen defects:

[0068] The CoFe MOF material obtained in step (3) is placed in a 0.1M NaOH aqueous solution and etched at room temperature for 10 hours. After the reaction is completed, the material is taken out, and the foamed nickel is rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain a CoFe LDH material rich in oxygen defects;

[0069] (5) Preparation of S-Ov-CoFe LDH material:

[0070] The oxygen-deficient CoFe LDH material obtained in step (4) is placed in a 0.1M C2H5NS (thioacetamide) aqueous solution and reacted at 60°C for 2h. After the reaction is completed, the material is taken out, and the nickel foam is rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain the S-Ov-CoFe LDH material.

[0071] Embodiment 3:

[0072] This embodiment relates to a method for preparing a defect site S-filled CoFe-LDH catalyst (S-Ov-CoFe LDH) material, the material comprising a nickel foam substrate and cobalt-iron-based hydrotalcite grown on the surface of the nickel foam substrate, comprising the following steps:

[0073] (1) Substrate cleaning: same as in Example 1;

[0074] (2) Preparation of CoFe LDH material:

[0075] 3.33 mmol of cobalt nitrate hexahydrate, 1.66 mmol of ferric nitrate nonahydrate, 4.33 mmol of urea and 2.16 mmol of ammonium fluoride are placed in 30 mL of deionized water and stirred for 20 minutes to obtain a mixed solution; the mixed solution is transferred to a 50 mL reactor, and a piece of nickel foam obtained in step (1) is placed in the reactor as a substrate, and the reactor is placed in a 150° C. oven for reaction for 8 hours; after the reaction is completed, the reactor is cooled to room temperature, and then the nickel foam with the material is taken out, and the nickel foam is rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain CoFe LDH material;

[0076] (3) Preparation of CoFe MOF materials:

[0077] 0.5 mmol of benzoic acid was placed in 30 ml of N,N-dimethylformamide and ultrasonicated for 1 h, and then transferred to a 50 ml reactor, and the pure CoFe LDH material obtained in step (2) was added to the reactor, and then the reactor was placed in a 200° C. oven for reaction for 10 hours; after the reaction was completed, the reactor was cooled to room temperature, and then the reacted material was taken out, and the foamed nickel was rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain the CoFe MOF material;

[0078] (4) Preparation of CoFe LDH materials rich in oxygen defects:

[0079] The CoFe MOF material obtained in step (3) is placed in a 0.1M KOH aqueous solution and etched at room temperature for 8 hours. After the reaction is completed, the material is taken out, and the nickel foam is rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain a CoFe LDH material rich in oxygen defects;

[0080] (5) Preparation of S-Ov-CoFe LDH material:

[0081] The oxygen-deficient CoFe LDH material obtained in step (4) is placed in a 0.1M sodium sulfide nonahydrate aqueous solution at 90°C for reaction for 1 hour. After the reaction is completed, the material is taken out, and the nickel foam is rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain the S-Ov-CoFe LDH material.

[0082] Embodiment 4:

[0083] This embodiment relates to a method for preparing a defect site S-filled CoFe-LDH catalyst (S-Ov-CoFe LDH) material, the material comprising a nickel foam substrate and cobalt-iron-based hydrotalcite grown on the surface of the nickel foam substrate, comprising the following steps:

[0084] (1) Substrate cleaning: same as in Example 1;

[0085] (2) Preparation of CoFe LDH material:

[0086] 2.55 mmol of cobalt nitrate hexahydrate, 2.55 mmol of ferric nitrate nonahydrate, 4.33 mmol of urea and 2.16 mmol of ammonium fluoride are placed in 30 mL of deionized water and stirred for 20 minutes to obtain a mixed solution; the mixed solution is transferred to a 50 mL reactor, and a piece of nickel foam obtained in step (1) is placed in the reactor as a substrate, and the reactor is placed in a 120° C. oven for reaction for 8 hours; after the reaction is completed, the reactor is cooled to room temperature, and then the nickel foam with the material is taken out, and the nickel foam is rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain CoFe LDH material;

[0087] (3) Preparation of CoFe MOF materials:

[0088] 0.5 mmol of phthalic acid was placed in 30 ml of N,N-dimethylformamide and ultrasonicated for 1 hour, and then transferred to a 50 ml reactor, and the CoFe LDH material obtained in step (2) was added to the reactor, and the reactor was placed in an oven at 180° C. for reaction for 12 hours; after the reaction was completed, the reactor was cooled to room temperature, and then the converted material was taken out, and the foamed nickel was rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain the CoFe MOF material;

[0089] (4) Preparation of CoFe LDH materials rich in oxygen defects:

[0090] The CoFe MOF material obtained in step (3) is placed in a 0.1M NaOH solution and etched at room temperature for 12 hours. After the reaction is completed, the material is taken out, and the nickel foam is rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain a CoFe LDH material rich in oxygen defects;

[0091] (5) Preparation of S-Ov-CoFe LDH material:

[0092] The oxygen-deficient CoFe LDH material obtained in step (4) is placed in a 0.1M thiourea aqueous solution at 100°C for reaction for 0.5h. After the reaction is completed, the material is taken out, and the nickel foam is rinsed with deionized water and anhydrous ethanol in turn, dried, and stored to obtain the S-Ov-CoFe LDH material.

[0093] Embodiment 5:

[0094] This example relates to the performance test of the S-Ov-CoFe LDH material prepared in Example 1, and its electrochemical performance is tested. The test method is as follows: the material is used as a working electrode, a Hg / HgO electrode is used as a reference electrode, and a graphite rod electrode is used as a counter electrode to form a three-electrode system, and the electrolyte is a 1M KOH aqueous solution. 5-Hydroxymethylfurfural (HMF) is added to the electrolyte, and the final concentration of HMF is 50mM. The current density-voltage relationship and the stability of the electrode are tested when the S-Ov-CoFe LDH electrode electrocatalyzes the oxidation of HMF, and the oxidation performance of HMF is tested for five consecutive electrolysis at a constant potential of 1.4V vs RHE. The test results are as follows: Figure 6-8 shown.

[0095] The CoFe LDH material was used as the working electrode for electrocatalytic oxidation of HMF to conduct a comparative test to test the relationship between current density and voltage. The results are as follows Figure 6 As shown. Figure 6It can be seen that defect filling can improve the HMFOR performance by regulating the band structure. On the one hand, the sulfur atom filling of the defect site can compensate for part of the missing coordination number and form electron orbital hybridization with the coordinated metal, weakening the excessive adsorption caused by excessive oxygen vacancies from two aspects: the number of external vacancies and the regulation of the internal electronic structure. On the other hand, the introduction of sulfur atoms can regulate the degree of electron localization, thereby affecting the number of direct catalytic sites during the reaction. The introduction of S partially fills the oxygen vacancies in the second shell and modulates the d band structure by forming metal-S bonds. Benefiting from the optimization of the adsorption behavior of HMF and OH species caused by S filling of the defect site, the acceleration of the interfacial charge transfer behavior, and the rapid formation of high-valence catalytic sites in the reaction, compared with pure CoFe LDH, the material exhibits excellent HMF oxidation activity, including a significantly advanced reaction potential and a 4-fold higher current density at 1.4V.

[0096] from Figure 7 It can be seen that after 60,000 s of electrolysis, the material still has a current density that is no different from that of the initial electrolysis, indicating that the S-Ov-CoFe LDH material has excellent stability.

[0097] from Figure 8 It can be seen that after five consecutive electrolysis cycles at a constant potential of 1.4 V vs RHE, the FE Faradaic efficiency of HMF for 2,5-furandicarboxylic acid (FDCA) remained at around 97%, and the FDCA yield remained above 95%.

[0098] This example also tests the S-Ov-CoFe LDH catalyst prepared in Example 1 and other catalysts at 10 mA cm -2 The required potential is as follows: Fig. 9 shown.

[0099] from Fig. 9 It can be seen that when the current density is 10 mA cm -2 When , the potential of S-Ov-CoFe LDH is only 1.26 V, which is significantly lower than that of other catalysts.

Claims

1. A method for preparing a CoFe LDH catalyst, characterized in that: The oxygen-defect-rich CoFe LDH material is treated by sulfur immersion to obtain a defect-site sulfur-filled CoFe LDH catalyst material.

2. The method for preparing the CoFe LDH catalyst according to claim 1, characterized in that: The sulfur immersion treatment is to immerse the oxygen-defective CoFe LDH material into a sulfur-containing solution, and the treatment conditions are: keeping warm at 60-100° C. for 0.5-2 hours.

3. The method for preparing the CoFe LDH catalyst according to claim 1, characterized in that: The sulfur-containing solution is a sodium thiosulfate pentahydrate aqueous solution, a sodium sulfide nonahydrate aqueous solution, a thiourea aqueous solution or a thioacetamide aqueous solution.

4. The method for preparing the CoFe LDH catalyst according to claim 1, characterized in that: The preparation method of the oxygen-defect-rich CoFeLDH material is: (1) Synthesize CoFe LDH materials by hydrothermal method; (2) Converting the CoFe LDH material into CoFe MOF material by solvothermal method; (3) Using CoFe MOF material as a precursor, etching with alkaline solution at room temperature can obtain oxygen-defect-rich CoFe LDH material.

5. The method for preparing the CoFe LDH catalyst according to claim 4, characterized in that: The hydrothermal condition is: keeping warm at 120-160°C for 4-8 hours; the solvent thermal condition is: keeping warm at 180-200°C for 10-12 hours; the etching condition is: keeping warm at room temperature for 3-12 hours.

6. The method for preparing the CoFe LDH catalyst according to claim 4, characterized in that: The specific steps of step (1) are: mixing the cobalt salt and the iron salt evenly to obtain a mixed solution, reacting the mixed solution with a substrate under hydrothermal conditions, and taking out the substrate after the reaction, namely the CoFe LDH material.

7. The method for preparing the CoFe LDH catalyst according to claim 6, characterized in that: The molar ratio of the cobalt salt to the iron salt is 1-4:1, and the molar ratio of the cobalt ions in the cobalt salt to the iron ion atoms in the iron salt is 24-30:10-18.

8. The method for preparing the CoFe LDH catalyst according to claim 6, characterized in that: The cobalt salt is cobalt nitrate or cobalt chloride; the iron salt is iron nitrate or iron chloride.

9. The defect-site sulfur-filled CoFe LDH catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the defective sulfur-filled CoFe LDH catalyst according to claim 9 in electrocatalytic oxidation of HMF, characterized in that: Used for electrocatalytic oxidation of 5-hydroxymethylfurfural to produce 2,5-furandicarboxylic acid.

Citation Information

Cited By

  • Preparation method and application of hollow CoFe-LDH / Co-MOF composite electrocatalyst

    CN117568859A